2023
DOI: 10.3390/geosciences13050131
|View full text |Cite
|
Sign up to set email alerts
|

Geological Uniqueness and Potential Geotouristic Appeal of Murge and Premurge, the First Territory in Puglia (Southern Italy) Aspiring to Become a UNESCO Global Geopark

Abstract: At the end of November 2021, a large area of Puglia (an administrative region in Southern Italy) was officially nominated as new aUGGp (aspiring UNESCO Global Geopark) by the Italian National Commission of UNESCO. This area comprises the northwestern part of the Murge territory, where a Cretaceous sector of the Apulia Carbonate Platform crops out, and part of the adjacent Premurge territory (where the southwestward lateral continuation of the same platform, being flexed toward the Southern Apennines Chain) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…An aspiring UNESCO Geopark first and foremost requires geological uniqueness with geotourism potential [80]. Thus, when surveying the tourism objective a researcher must first check how the objective responds to five attributes: age, uniqueness, originality, size, and function fulfilled [4].…”
Section: Singularity (Rarity)mentioning
confidence: 99%
“…An aspiring UNESCO Geopark first and foremost requires geological uniqueness with geotourism potential [80]. Thus, when surveying the tourism objective a researcher must first check how the objective responds to five attributes: age, uniqueness, originality, size, and function fulfilled [4].…”
Section: Singularity (Rarity)mentioning
confidence: 99%
“…By attracting visitors, mountain areas offer a sustainable development strategy according to Romeo et al [24]. In fact, the Arouca Declaration (2011) states that tourism can sustain and enhance the identity of a territory, taking into consideration its geology, environment, culture, aesthetics, heritage, and the well-being of its residents [25]. In Slovenia's mountain regions, Trček and Koderman [26] found that sustainable tourism was an important development policy suitable for the conservation of protected mountainous natural and cultural landscapes facing intense depopulation and loss of agricultural land.…”
Section: Mountain Areasmentioning
confidence: 99%
“…Agriculture in Murgia was limited to flat valleys and depression bottoms where fertile soil had accumulated. The barren karst areas outside of these -The Murgia area, also known as 'le Murge' in Italian, is situated in the centre of the Puglia region [25]. The rural area of Alta Murgia, which is the highest plateau in the Murgia area, contains Italy's first National Rural Park (approximately 68 ha), created in 2004 [36], and boasts numerous significant historical, archaeological, and paleontological sites [4].…”
mentioning
confidence: 99%
“…Different authors have emphasized their significance from a geotouristic point of view, using UGGps but also other geosites as local touristic products that offer a framework of a holistic geotouristic approach by setting a link between culture and nature [46,47]. They can also be linked with Sustainable Development Goals [48], and on their official websites, many UGGps present materials that can be used both on-site and off-site [49].…”
Section: Geoheritage: Outdoor Learning and Science Educationmentioning
confidence: 99%